The Force of Numbers: Investigating Manual Signatures of Embodied Number Processing - Miklashevsky, Alex; Lindemann, Oliver; Fischer, Martin H. (Frontiers in Human Neuroscience, 2021)
The study has two objectives: (1) to introduce grip force recording as a new technique for studying embodied numerical processing, and (2) to demonstrate how three competing accounts of numerical magnitude representation can be tested by using this new technique: the Mental Number Line, A Theory Of Magnitude and Embodied Cognition (finger counting-based) account. While 26 healthy adults processed visually presented single digits in a go/no-go n-back paradigm, their passive holding forces for two small sensors were recorded in both hands. Spontaneous and unconscious grip force changes related to number magnitude occurred in the left hand already 100-140 ms after stimulus presentation and continued systematically. Our results support a two-step model of number processing where an initial stage is related to automatic activation of all stimulus properties whereas a later stage consists of deeper conscious processing of the stimulus. This interpretation generalizes previous work with linguistic stimuli and elaborates the timeline of embodied cognition. We hope that the use of grip force recording will advance the field of numerical cognition research.